Tannins in Terminalia bellirica inhibit hepatocellular carcinoma growth by regulating EGFR-signaling and tumor immunity. Issue 8 (7th April 2021) - Chang, Zihao; Jian, Ping; Zhang, Qiunan; Liang, Wenyi; Zhou, Kun; Hu, Qian; Liu, Yuqi; Liu, Runping; Zhang, Lanzhen
Abstract : TB-TF inhibited the proliferation and survival of HCC by regulating the EGFR signaling pathway and by modulating the immunosuppressive tumor microenvironment. Abstract : The fruits of Terminalia bellirica (Gaertn.) Roxb. (TB) are used as a multi-use therapeutic herbal product in the Tibetan medicinal system and are prescribed as a general health tonic in the traditional Ayurvedic medicinal system. It has been demonstrated that these fruits have a variety of pharmacological activities, including anti-tumor, anti-oxidative, anti-inflammatory, hepatoprotective and immunoregulatory effects, etc. However, the therapeutic effects of tannins in TB on HCC and the underlying mechanisms remain uncharacterized. In the current study, we aimed to identify the anti-tumor effect of tannins in TB by employing a H22 xenograft mouse model and by performing cell-based in vitro studies with the assistance of the network pharmacology analysis. The crude extract of TB was purified to yield total tannin fraction (TB-TF), and our results found that TB-TF significantly inhibited the tumor growth of H22 xenografts in mice by inducing apoptosis and reducing angiogenesis. A total of 90 compounds were then identified in TB-TF by UPLC-MS/MS, and 27 were found in serum after oral administration of TB-TF in mice. The network pharmacology analysis based on these absorbed components was performed and, along with experimental evidence, it revealed that the ERBB, PI3K-Akt, and MAPK signaling pathways may be involved in the anti-tumor effect of TB-TF on HCC. Furthermore, we suggested that TB-TF effectively modulated the immunosuppressive tumor microenvironment in H22 xenograft mice. In summary, our study demonstrated that TB-TF could be developed as a functional food, which is not only a promising anti-cancer reagent but also a potential candidate with bright prospects for the emerging trends of immunotherapy for HCC.